2021
DOI: 10.3390/nu13051519
|View full text |Cite
|
Sign up to set email alerts
|

Curcuma Longa, the “Golden Spice” to Counteract Neuroinflammaging and Cognitive Decline—What Have We Learned and What Needs to Be Done

Abstract: Due to the global increase in lifespan, the proportion of people showing cognitive impairment is expected to grow exponentially. As target-specific drugs capable of tackling dementia are lagging behind, the focus of preclinical and clinical research has recently shifted towards natural products. Curcumin, one of the best investigated botanical constituents in the biomedical literature, has been receiving increased interest due to its unique molecular structure, which targets inflammatory and antioxidant pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 152 publications
(202 reference statements)
0
7
0
Order By: Relevance
“…A number of experimental studies have shown the potent anti-oxidant and antiinflammatory properties of curcumin and its protective effects against AD in animal models [229], while few RCTs and case reports are available [230][231][232][233][234]. A study involving thirty-four AD patients receiving either 1 or 4 g/d of curcumin or placebo for six months found no significant effects in MMSE [230].…”
Section: Curcuminmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of experimental studies have shown the potent anti-oxidant and antiinflammatory properties of curcumin and its protective effects against AD in animal models [229], while few RCTs and case reports are available [230][231][232][233][234]. A study involving thirty-four AD patients receiving either 1 or 4 g/d of curcumin or placebo for six months found no significant effects in MMSE [230].…”
Section: Curcuminmentioning
confidence: 99%
“…Turmeric supplements generally have low bioavailability, which is why new formulations have been proposed, such as polymeric micelles, polymer nanoparticles, nanogels, dendrimers, nanoemulsions, inclusion complexes, phytosomes, solid-lipid nanoparticles, curcumin nanoparticles, liposomes nanoparticles, liposomes, micelles, nanogel, dendrimers, nanoemulsions, inclusion complexes, and phytosomes with potential to reduce intestinal degradation and increase curcumin bioavailability, ultimately enhancing its efficacy throughout the body and the brain [229].…”
Section: Curcuminmentioning
confidence: 99%
“…Metabolic dysfunction that is associated with oxidative stress and inflammation may greatly accelerate the onset and worsen the progression of cognitive dysfunctions by promoting brain ageing and reducing lifespan. Berry et al [ 5 ] integrate current knowledge on the mechanisms underlying cognitive decline, highlighting the potential role of curcumin in this highly disabling and prevalent condition in the aging population which greatly affects physical health and quality of life. Natural antioxidant agents such as curcumin have pleiotropic protective effects and appear ideal to prevent or treat conditions such as Alzheimer’s disease or cognitive decline, whose origin is multifactorial.…”
mentioning
confidence: 99%
“…Curcumin, a constituent compound of Curcuma longa plants, has various pharmacological properties, including anti-oxidant, anti-inflammatory, anti-bacterial, anti-viral, anti-cancer, and anti-diabetic properties (47,48). A clinical study showed that curcumin was safe even at doses of up to 8 g per day (20).…”
Section: Discussionmentioning
confidence: 99%